Effect of Moment of Inertia of Attached Mass on Natural Frequencies of Cantilevered Symmetrically Laminated Plates - Kenji Hosokawa (EPI International Journal of Engineering, 2018)
Since composite materials such as laminated composite plates have high specific strength and high structural efficiency, they have been usedin many structural applications. It is therefore very important to make clear the vibration characteristics of the laminated plates for the designand the structural analysis. Especially, the vibration characteristics of the laminated plates with attached mass are essential. However, wecannot find the theoretical or experimental approaches for the free vibration of laminated plates with attached mass. In the present study, theexperimental and numerical approaches are applied to the free vibration of cantilevered symmetrically laminated plates with attached mass.First, by applying the experimental modal analysis technique to the cantilevered symmetrically laminated plates with attached mass, thenatural frequencies and mode shapes of the plates are obtained. Next, the natural frequencies and mode shapes of the cantileveredsymmetrically laminated plates with attached mass are calculated by Finite Element Method (FEM). Finally, from the experimental andnumerical results, the effect of the moment of inertia of the attached mass to the natural frequencies and mode shapes of the cantileveredsymmetrically laminated plates are clarified.